Aplikasi Probiotik, Prebiotik dan Sinbiotik melalui Pakan untuk Meningkatkan Respon Imun dan Kelangsungan Hidup Ikan Nila Oreochromis niloticus yang Diinfeksi Streptococcus agalactiae (Application of Probiotic, Prebiotic and Synbiotic through Feed for Increasing Immune Response and Survival Rate of Nile Tilapia Oreochromis niloticus Infected by Streptococcus agalactiae) - Widanarni Widanarni; Achmad Farouq; Munti Yuhana (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2014)
In this study, fish feed supplemented by probiotic, prebiotic and synbiotic were applied to enhance the immune response and survival rate of the fish against Streptococcus agalactiae infection. Treatments used in this study, were as follows: feed containing 1% (v/v) of probiotic (C), feed containing 2% (v/v) of prebiotic (D) and feed containing mixed of 1% (v/v) of probiotic + 2% (v/v) of prebiotic (E, defined as synbiotic). Control fish (both positive, A; and negative, B; treatments) were fed by fish feed without containing neither probiotic nor prebiotic. In this study, test fish used monosex (all male) red tilapia with the average of body weight of 13,43±2,97 gram. The fish were fed by supplemented feed within first 30 days pre injection. After that, the treated fish were challenged by 109 CFU/ml of S. agalactiae. Nile tilapia fed by synbiotic (treatment E) had higher immune response (haemoglobin, neutrofil, and phagocyte indices) than control, but were not significantly different than those of treatment C, and D. After challenged test by S. agalactiae, treatment C, D and E resulted significantly higher resistance than that of control. The survival rate of fish fed by supplemented feed containing probiotic (C), prebiotic (D) and synbiotic (E) were 76%, 76% and 80%, respectively; higher than than positive control (50%). The results showed that addition of probiotic, prebiotic and synbiotic in fish feed could increase immune response and survival rate against S. agalactiae.Keywords : tilapia, probiotic, prebiotic, synbiotic, Streptococcus agalactiae